Silvopastoral Systems Enhance Soil Quality in Grasslands of Colombia - Judith Martínez; Yasmín S. Cajas; Juan D. León; Nelson W. Osorio (Applied and Environmental Soil Science)
In the tropical drylands of Colombia, the soils subjected to traditional systems of livestock production are severely degraded and depleted of plant nutrients. Multistrata silvopastoral systems are viable alternatives to improve livestock production; however, it is unknown whether these systems can reduce the negative environmental impacts of traditional systems on soil quality. The objective of this study was to evaluate the effects of 13-year-old multistrata silvopastoral systems on soil quality parameters in degraded soils of the Sinu River Valley, Colombia. The results show that the trees in the silvopastoral systems increased or maintained soil pH values and nutrient availability (phosphorus, potassium, and calcium) with respect to the pastures with only grasses. The effects were significantly controlled by the types of plant species, particularly Guazuma ulmifolia and Cassia grandis.